E-Commerce Implementation Strategy for the Development of Micro, Small, and Medium Enterprises (MSMEs) in East Lombok Regency, West Nusa Tenggara - Sulaeman Sulaeman; Harbyanto Junarta; Ma’ruf Alqifari Ma’ruf Alqifari (Business Management, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the national economy, particularly in creating employment opportunities, increasing community income, and supporting regional economic growth. However, the development of the digital era requires MSMEs to adapt to technology in order to improve their business competitiveness. One strategy that can be implemented is the utilization of e-commerce as a means of marketing and business development. This study aims to analyze e-commerce implementation strategies for MSME development in East Lombok through a literature review approach. The method used in this research is a literature study by collecting and analyzing various previous studies relevant to the implementation of e-commerce in MSMEs. The results of the study indicate that the implementation of e-commerce has a positive influence on MSME development, particularly in increasing market reach, sales volume, operational efficiency, and business competitiveness. In East Lombok, the use of e-commerce has been proven to help MSME actors market local products more widely through digital platforms such as marketplaces and social media. The main factors supporting successful e-commerce implementation include technological readiness, business innovation, a supportive environment, and human resource capacity. Nevertheless, several obstacles remain, such as low digital literacy, limited infrastructure, and lack of sustainable assistance. Therefore, training support, mentoring, and strengthening of digital infrastructure are needed to ensure that e-commerce adoption can run optimally and sustainably in supporting MSME development in the digital economy era.